Analisis Faktor Penyebab Kecemasan Belajar Matematika Siswa Kelas X SMK Tunas Pembangunan - Syifa Fauziyah; Nur Amalia; Putri Amelia (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
The aim of this research is to describe what factors cause students' anxiety about learning Mathematics. This type of research is a descriptive qualitative approach. The subjects of this research were class X students majoring in Culinary and Office Management at Tunas Pembangunan Vocational School, South Jakarta. Research data was collected using questionnaires and interviews. The results of the research show that the anxiety of studying Mathematics experienced by class and anxious. Factors that cause moderate level anxiety are that learning Mathematics is too monotonous so that students quickly feel bored and causes students to feel afraid if their Mathematics grades do not match expectations. Meanwhile, the factors that cause low levels of anxiety are not feeling afraid when studying Mathematics and considering Mathematics as a fun subject so that students like Mathematics.